Increased Formation of Follicular Antrum in Aquaporin-8-Deficient Mice Is Due to Defective Proliferation and Migration, and Not Steroidogenesis of Granulosa Cells - Wang, Dejiang; Di, Xiangjun; Wang, Jie; Li, Miao; Zhang, Di; Hou, Yaxin; Hu, Jiao; Zhang, Ge; Zhang, He; Sun, Meiyan; Meng, Xiangyu; Sun, Bo; et al. (Frontiers in Physiology, 2018)
Aquaporin-8 (AQP8) is a water channel protein expressed exclusively in granulosa cells (GCs) in mouse ovary. Our previous studies of AQP8-deficient (AQP8-/-) mice demonstrated that AQP8 participates in folliculogenesis, including in the formation of follicles, ovulation, and atresia. However, its physiological function in formation of the antral follicle is still largely unknown. In the present study, we observed significantly increased numbers of antral follicles in AQP8-/- ovaries as well as significantly increased follicular antrum formation in in vitro 3D culture of AQP8-/- follicles. Functional detection of AQP8-/- GCs indicated that cell proliferation is impaired with FSH treatment, and wound healing and Transwell migration are also impaired with or without FSH treatment,compared with that in WT. However, the biosynthesis of estradiol and progesterone as well as the mRNA levels of key steroidogenic enzyme genes (CYP19A1 and StAR) in AQP8-/- GCs did not change, even with addition of FSH and/or testosterone. In order to estimate the influence of the impaired proliferation and migration on the density of GC mass, preantral follicles were injected with FITC-dextran, which distributes only in the intercellular space, and analyzed by confocal microscopy. The micrographs showed significantly higher transmission of fluorescence in AQP8-/- follicles, suggesting increased intercellular space of GCs. Based on this evidence, we concluded that AQP8 deficiency leads to increased formation of follicular antra in vivo and in vitro, and the mechanism may be associated with increased intercellular space of GCs, which may be caused by defective proliferation and migration of GCs. This study may offer new insight into the molecular mechanisms of the formation of follicular antrum.